Fully anhydrous HCl electrolysis using polybenzimidazole membranes. (26th July 2022) - Likit-anurak, Kris; White, Rembert; Murdock, Laura A.; Benicewicz, Brian C.; Shimpalee, Sirivatch; Meekins, Benjamin H.
Abstract: We demonstrate for the first time a fully anhydrous gas-phase hydrogen chloride electrolyzer. By taking advantage of polybenzimidazole's (PBI) low membrane resistivity in anhydrous conditions (0.87 ± 0.57 Ω-cm 2 at 160 °C) and its temperature and acid environment stability, we are able to directly convert pure hydrogen chloride gas to dry hydrogen and dry chlorine at efficiencies nearing 100% at an electrolyzer temperature of 160 °C and electrolyzer potential of 1.8 V. Finally, we discuss steps to further improve this electrolysis process in terms of both electrolyzer performance and cost reduction. Graphical abstract: Image 1 Highlights: 1st demonstration of completely anhydrous electrolysis of HCl(g). Single pass conversion efficiency greater than 93%. para- PBI area-specific resistance of 0.87 (±0.57) Ω-cm 2 at 160 °C under 100% HCl. Demonstrates utility of polybenzimidazole membranes for atypical electrolysis.